Effect of Time of Initiation of Feeding after Hatching and Influence of Dietary Ascorbic Acid Supplementation on Productivity, Mortality and Carcass Characteristics of Ross 308 Broiler Chickens in South Africa - Mbajiorgu, C.A.; Ng`ambi, J.W.; Norris, D. (International Journal of Poultry Science, 2007)
An experiment was conducted to evaluate the effect of time of initiation of feeding after hatching and influence of dietary ascorbic supplementation during realimentation on productivity, carcass characteristics and mortality of Ross 308 broiler chickens. The study was a factorial arrangement in a complete randomized design. Six hundred and seventy five unsexed Ross 308 broiler chickens with an initial weight of 32±2 g per bird were assigned to 15 treatments in a 3 (times of initiation of feeding) x 5 (ascorbic acid supplemental levels) factorial arrangement with three replications, each having 15 birds each. The experimental diets were isocaloric and isonitrogenous but with different ascorbic acid supplementation levels. Ascorbic acid supplementation started three days after hatching. More than 50% of the birds died between one and three days of age when initiation of feeding after hatching was above 36 hours. Time of initiation of feeding above 36 hours of hatching resulted in lower (p